Evaluation of polarising stimuli on bone marrow-derived macrophage phenotypes in two models of neuroinflammation - Barrett, James (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
Inflammatory changes in the brain have been observed with aging and in neurodegenerative disorders, and these are believed to be associated with the accompanying decline in cognitive function. Recent evidence has suggested that peripheral immune cells may play a role in the modulation of inflammatory events within the central nervous system. The objective of this thesis was to investigate the responses of macrophages prepared from aged rats and mice which overexpress amyloid precursor protein and presenilin 1 (APP/PS1 mice) to stimuli which have been shown to polarise macrophages to different activation states. Therefore, the effects of lipopolysaccharide (LPS) and interferon-γ (IFNγ), which induce classical activation of macrophages, which is also referred to as the M1 phenotype, and interleukin-4 (IL-4), which induces alternative activation, also referred to as the M2 state, were compared in bone marrow-derived macrophages (BMDMs) from young and aged rats and BMDMs from wildtype (WT) and APP/PS1 mice.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin